Assessment of groundwater metals contamination using geoelectric methods and pollution index around nickel mine Pomalaa District, Kolaka Regency, Southeast Sulawesi - Sugiono Nur Robithotul; Masitoh Ferryati; Mararis Denis; Kurniawan (BIO Web of Conferences)
Nickel mining operations can significantly impact groundwater quality by releasing metallic contaminants. This study aims to quantify metal concentrations in groundwater quality changes at nickel mining sites in Pomalaa District, Kolaka Regency. The study employs the Wenner configuration geoelectric technique and Pollution Index (IP) to assess metal pollution in groundwater. Geoelectric data, log borings, laboratory results of groundwater quality, and regional geological maps were used in the study. Water sample analysis detected toxic elements such as Aluminum, Iron, Manganese, Zinc, Copper, Hexavalent Chromium, Nickel, Cobalt, Cadmium, and Lead. Geoelectric analysis shows that groundwater is generally found within fracture zones of igneous and metamorphic rocks at depths between 2 and 100 meters. The Pollution Index (IP) categorized the groundwater samples as moderately contaminated, failing to meet drinking water quality standards. The analysis suggests that the groundwater originates from fissures in ultramafic rock, with significant metal contamination detected in groundwater wells. Metal content in groundwater occurs due to the interaction between rocks and groundwater. The study results also show that the groundwater pollution index is in the light category. However, the levels of heavy metals mean that groundwater cannot be directly used to fulfill needs. Further processing of groundwater is necessary so that groundwater can be used.